A revista Chiapas e o debate intelectual sobre a política neoliberal e o movimento zapatista no México (1995-2004) - Mahira Caixeta Pereira da Luz (2019)
The publication Chiapas, our object of research, was a co-edition published by the Instituto de Investigaciones Económicas (IIEC), of the Universidad Nacional Autónoma de México, in a partnership with Ediciones Era. The academic publication, which was directed by the economist Ana Esther Ceceña, circulated in both digital and print editions, its duration going the year 1995 to 2004. Its creation was motivated by an armed insurrection — which took place in 1994 in Mexico — of the Zapatista Army of National Liberation (EZLN), an indigenous social movement. The scholars who developed it had as a starting objective to analyze the formation of the movement and how its performance affected the state of Chiapas and Mexico as a whole, scope which was gradually widened. Our study has the goal of understanding in what ways the publication Chiapas configured itself as an intellectual space of resistance and opposition, both to neoliberalism and to the flaws in the process of building up democracy in the political scenario of Mexico. In order to do that, we have analyzed, through the published articles, the relationship that this publication established with the EZLN, with the society it was inserted in and what ideas surrounded the publication. We have used the Intellectual History as theoretical foundation, as well as magazines as source for the work of the historian. Our emphasis was on the analysis of the ideas that surrounded the journal and how they related to the society in which they were built.